Effects of mycophenolate mofetil introduction in liver transplant patients: results from an observational, non‐interventional, multicenter study (LOBSTER). (13th February 2013) - Schlitt, Hans J.; Jonas, Sven; Ganten, Tom M.; Grannas, Gerrit; Moench, Christian; Rauchfuss, Falk; Obed, Aiman; Tisone, Giuseppe; Pinna, Antonio D.; Gerunda, Giorgio E.; Beckebaum, Susanne
Abstract The benefits of calcineurin inhibitor (CNI)‐sparing regimens on renal function following liver transplantation (LT) have been demonstrated in clinical studies. This observational study assessed the real‐life effects of mycophenolate mofetil (MMF) introduction in LT patients. Four hundred and ninety‐seven patients in whom MMF was introduced according to local standards or clinical considerations were entered. Patients were grouped by time between transplantation and start of MMF (start of study): Group A (n = 263): ≤6 d; Group B (n = 64): >6 d to ≤1 month; Group C (n = 74): >1 month to ≤1 yr; and Group D (n = 96): >1 yr. CNI sparing occurred in all groups, particularly in Groups C and D. Mean MMF doses at 12 months were 1202.7, 1363.5, 1504.7, and 1578.1 mg/d, respectively, in Groups A–D. At introduction of MMF, median glomerular filtration rate was 73.3, 81.7, 62.7, and 53.7 mL/min/1.73 m2 in Groups A–D. At 12 months, this decreased to 66 mL/min/1.73 m2 in Groups A and B, remained stable in Group C, and increased in Group D (64.8 mL/min/1.73 m2). Serious adverse drug reactions were lowest in Group D. In conclusion, MMF with a subsequent decrease in CNI was well tolerated and improved renal function even years after transplantation. A more forceful MMF dosing strategy with greater CNI sparing may further improve renal function.